A STOCHASTIC APPROACH TO EVALUATE THE RELIABILITY OF URBAN PASSENGER TRANSPORTATION SERVICES - Kopytkov, D.; Копытков, Д. М.; Копитков, Д. М. (Харьковский национальный автомобильно-дорожный университет, 2017)
An approach to estimate the reliability of urban passenger transport from the passengers' viewpoint has been presented, in which the parameter to be investigated is the fixed-route headway. The probability of passenger arrival to the destination point has been suggested as an indicator of the service reliability. The given approach makes it possible to evaluate the reliability of both single modes of the urban mass transit and the transportation system reliability as a whole.
ВЕРОЯТНОСТНЫЙ ПОДХОД К ОПРЕДЕЛЕНИЮ НАДЕЖНОСТИ ПРЕДОСТАВЛЕНИЯ УСЛУГ ГОРОДСКОГО ПАССАЖИРСКОГО ТРАНСПОРТА
ІМОВІРНІСНИЙ ПІДХІД ДО ВИЗНАЧЕННЯ НАДІЙНОСТІ НАДАННЯ ПОСЛУГ МІСЬКОГО ПАСАЖИРСЬКОГО ТРАНСПОРТУ
Keywords: urban mass transit; reliability; headway; law of distribution; arrival probability; надежность; интервал движения; вероятность прибытия в пункт назначения; закон распределения; надійність; інтервал руху; імовірність прибуття до пункту призначення; закон розподілу; 656.025.2=111